Investigating the association of chemokine receptor 5 (CCR5) polymorphism with cervical cancer in human papillomavirus (HPV) positive patients = Investigação da associação do polimorfismo do receptor de quimiocinas CCR5 com câncer cervical em pacientes HPV positivos - Patrícia Sayuri Suzuki; Karen Brajão de Oliveira; Mateus Nóbrega Aoki; Vera Lúcia Hideko Tatakihara; Sueli Donizete Borelli; Maria Angelica Ehara Watanabe (Universidade Estadual de Maringá, 2008)
HPV is one of the most frequent causes for the development of cervicalcancer. It is known that chemokines are important determinants of early inflammatory responses. The CC chemokine receptor 5 (CCR5) gene is involved in the chemotaxis of leukocytes toward inflammation sites. In the present study, polymerase chain reactions(PCR) in genomic DNA samples, using specific CCR5 oligonucleotide primers surrounding the breakpoint deletion, detected a 225 bp product from the normal CCR5 allele and a 193 bp product from the 32 bp deletion allele. The wild type genotype was prevalent in both group, but it was not statistically significant, with χ2 = 1.519 (2 degrees of freedom; p > 0.05). As there are a small number of D32 allele carriers, further studies are needed to clarify the role of CCR5 in the cervical cancer. O HPV é um dos maiores responsáveis pelo desenvolvimento do câncer cervical. É conhecido que as quimiocinas são importantes determinantes da resposta inflamatória precoce. O produto dogene do receptor de quimiocinas CCR5 está envolvido na quimiotaxia de leucócitos para sítios inflamatórios. No presente estudo, reações em cadeia da polimerase (PCR) de amostras de DNA genômico, utilizando iniciadores específicos para CCR5 que flanqueam a região de deleção, foram utilizadas para detectar produto de 225 bp para o alelo normal e193 bp para o alelo que apresenta a deleção de 32 bp. O genótipo selvagem foi o mais prevalente em ambos os grupos e não houve diferença estatisticamente significativa, com χ2 = 1,519 (2 graus de liberdade; p > 0,05). Uma vez que a prevalência de indivíduosportadores do alelo D32 é pequena, são necessários mais estudos a fim de elucidar o papel do CCR5 no cancer cervical.